2022
DOI: 10.1038/s41467-022-35228-y
|View full text |Cite
|
Sign up to set email alerts
|

A growth selection system for the directed evolution of amine-forming or converting enzymes

Abstract: Fast screening of enzyme variants is crucial for tailoring biocatalysts for the asymmetric synthesis of non-natural chiral chemicals, such as amines. However, most existing screening methods either are limited by the throughput or require specialized equipment. Herein, we report a simple, high-throughput, low-equipment dependent, and generally applicable growth selection system for engineering amine-forming or converting enzymes and apply it to improve biocatalysts belonging to three different enzyme classes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…Structural modeling and molecular docking revealed that M226L opened the substrate tunnel and therefore increased its activity. 96 Similarly, after random and 19 °C and doubled the tolerance to DMSO. Mutagenesis in the tunnel affects the pathway of cosolvent molecules into the active site cavity, and the introduced substitutions close the tunnel and may prevent DMSO molecules from entering the active site and causing structural instability of the protein.…”
Section: Directed Evolution Of Tunnelmentioning
confidence: 99%
“…Structural modeling and molecular docking revealed that M226L opened the substrate tunnel and therefore increased its activity. 96 Similarly, after random and 19 °C and doubled the tolerance to DMSO. Mutagenesis in the tunnel affects the pathway of cosolvent molecules into the active site cavity, and the introduced substitutions close the tunnel and may prevent DMSO molecules from entering the active site and causing structural instability of the protein.…”
Section: Directed Evolution Of Tunnelmentioning
confidence: 99%
“…[5] So far, the most effective method of modifying substrate promiscuity, catalytic activity, and stereoselectivity of ATAs is to mutate crucial residues adjacent to the two binding pockets by protein engineering to alter their steric and electronic environment. [6] Recently, a series of rationaldesign or screening methods, such as structure-dependent rational design, [7] mechanism-guided computational design [8] and a growth selection [9] method, have been successfully applied to engineer ATAs for higher activity, broader substrate scope and improved stereoselectivity towards particular substrates. However, these strategies require a significant amount of computational and/or experimental effort to optimize the biocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrahighthroughput screening methods based on a variety of in vitro microscale (i.e. single-cell) compartmentalization 17 strategies or alternatively growth based selections 18,19 enable large library screening. However, these approaches may suffer from limitations such as requiring tailoring for a specific enzyme chemistry, necessitating microfluidic device design, fabrication, and utilization, or otherwise being limited in chemical scope.…”
Section: Introductionmentioning
confidence: 99%